Performance of Protective Clothing: Fourth Volume 1992
DOI: 10.1520/stp19149s
|View full text |Cite
|
Sign up to set email alerts
|

Ability of 1000 mL Water Leak Test for Medical Gloves to Detect Gloves with Potential for Virus Penetration

Abstract: Does the 1000 mL water leak test for medical gloves detect potential for virus penetration? Water leak and virus penetration were determined sequentially in hanging latex surgical gloves (4 brands) with 1000 ml of ΦX174-containing buffered saline (DPBS). Individual fingers (some punctured) were visually examined for water (DPBS) leaks for 2 minutes, then dipped into DPBS for 60 minutes for collection of virus that penetrated the latex barrier. Many punctured and a few non-punctured fingers leaked both water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…(5,6,15) A primary concern was the ability of the 1 L water-leak test to detect holes in the fingers and thumb. Preliminary investigation indicated this was an issue with holes made by a 21-gauge needle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,6,15) A primary concern was the ability of the 1 L water-leak test to detect holes in the fingers and thumb. Preliminary investigation indicated this was an issue with holes made by a 21-gauge needle.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility was anticipated based on the reported disparities from previous studies, (5,6) as well as on a report that indicated the inability of the water-leak test to identify holes in the index, middle, and ring fingers. (15) Most notably, the thumb and pinky regions were not evaluated in the previous studies, which was an area on concern. Thus, a standardized method was developed to detect holes in the finger, thumb, and palm regions.…”
Section: Methodsmentioning
confidence: 99%
“…FDA, 2008). Thus, selection of disposable gloves resides primarily on the 1-l water-leak test results, which has been shown to not adequately protect against viral penetration (Kotilainen et al, 1992). Alternative standards and guidance do evaluate viral penetration, namely ASTM F 1671 (ASTM International, 2007).…”
Section: Glove Integritymentioning
confidence: 99%
“…However, product formulation and variability are not addressed in these standards. This is further complicated by indications that the existing 1-l water-leak test for watertightness, which is a basis of many standards such as American Society for Testing and Materials (ASTM) D 5151, EN 455-1, and NFPA 1999, does not adequately detect small holes in the fingers and thumb that could pass a virus (Kotilainen et al, 1992;Phalen and Wong, 2011). The ASTM has a test method for evaluating viral penetration (ASTM International, 2007), ASTM F 1671, which is also used in the NFPA 1999 Standard (NFPA, 2008), but it is not designed for post-production quality control and quality assurance testing.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] For comparison, common pathogenic human viruses include hepatitis B (42 nm), human papilloma (45-55 nm), herpes simplex (120-150 nm), cytomegalovirus (120-150 nm), 16 and human immunodeficiency virus (90-130 nm). 17,18 The virus was assayed biologically (by infectivity) using standard microbiological methods, that is, the standard double agar layer method for coliphage plaque formation with E. coli C as the host bacterium.…”
Section: The Challenge Virusmentioning
confidence: 99%